A new hybrid decision-making framework to rank power supply systems for government organizations: A real case study. (October 2020) - Ramezanzade, Mohsen; Saebi, Javad; Karimi, Hossein; Mostafaeipour, Ali
Abstract: This paper aims to select the best hybrid renewable energy system (HRES) using a new multi-criteria decision-making model for supplying the power consumption of a government institution. The model considers social, environmental, technical, and economic criteria for providing a clear overview of the most suitable HRES design configurations. The proposed model has been implemented in two scenarios related to economic conditions. In this model, Analytic Hierarchy Process, Best-Worst, and Full Consistency methods are used for the weighting of criteria and Evaluation Based on Distance from Average Solution methods and Technique for Order of Preference by Similarity to Ideal Solution are used for selecting the best alternative. The results of the first scenario show that the crucial criteria were technical and social issues. Finally, alternative 4079 was the best alternative that included 450 kW converter capacity, 300 kW diesel generator, 550 kW photovoltaic systems, 800 kW battery storage, and 500 kW wind turbines and indolence of the main grid. In the second scenario, economic criteria were the fundamental criteria and the 4865th alternative was the best alternative that included the main grid, 130 kW converter capacity, 40 kW PV systems, 40 kW battery storage, and 40 kW wind turbines.